Drosophila Populations Reared Under Tropical Semi-natural Conditions Evolve Season-dependent Differences in Timing of Eclosion - Dani, Chitrang; Sheeba, Vasu (Frontiers in Physiology, 2022)
Circadian clocks are considered an evolutionary adaptation to environmental cycles, helping organisms to adapt to daily and seasonal changes. However, most studies on the evolution of circadian rhythms have been carried out in controlled laboratory conditions; hence evolution of circadian clocks and rhythms in organisms reared under the influence of naturally varying time cues is not well understood. To address this, we reared large outbred fly populations in an outdoor enclosure on our institutional grounds in Bengaluru, southern India for about 150 generations, at the same time maintaining their ancestral control populations under standard laboratory conditions. Studying their rhythms in eclosion, a vital behavior for Drosophila, in the laboratory and semi-natural environments revealed that flies reared under semi-natural conditions differed in the timing of eclosion under semi-natural conditions in a season-dependent manner from their laboratory-reared counterparts. These differences were manifested under harsh semi-natural environments but not under mild ones or in standard laboratory conditions. Further analysis revealed that this phenotype might be responsive to seasonal changes in temperature cycles which was confirmed in the laboratory with simulated light and temperature cycles that approximated semi-natural conditions. Our results highlight key intricacies on the relative impact of intensity and timing of environmental cues for predicting the timing of Drosophila eclosion under tropical naturalistic conditions. Overall, our research uncovers previously unexplored aspects of adaptive circadian timekeeping in complex natural conditions, offering valuable insight into the evolution of clocks.